Analysis Of Performance Assessment With The Balance Scorecard Approach And Development Strategy At Tenriawaru Bone Hospital In 2022 (Journal of Pharmaceutical Negative Results, 2023)
Performance measurement is an important factor for an organization, both now and in the future. The use of the Balanced Scorecard (BSC) concept is expected to reduce the weaknesses in performance measurement that are only oriented towards financial aspects as well as health service quality indicators. The purpose of this research is to analyze how performance is based on the Balanced Scorecard method at Tenriawaru Bone General Hospital. This study uses a mixed methods approach, namely qualitative and quantitative with a cross sectional approach. Collecting data using questionnaires, interviews, and Document Observation. To obtain data from the questionnaire, the sample in this study were 100 patients and 89 employees. The results show, based on the BSC approach, the learning and growth perspective obtained a score of 11.25, Internal Business Perspective 33.5, Customer Perspective 13, and Finance 19.5, from Tenriawaru the performance calculation of Tenriawaru Bone General Hospital obtained a score of 77.25 and was included in category A (good) from maximum category AAA (Very Good). It can be concluded that the lowest perspective is learning and growth. It is hoped that management evaluates all units for improving hospital performance in the future. For further research, it is better to examine the relationship or influence between perspectives on hospital performance.